KNOWLEDGE ON PREVENTION OF SURGICAL SITE INFECTION AMONG MEDICAL STAFF IN SON TAY GENERAL HOSPITAL, 2021 (Vietnam Journal of Community Medicine, 2021)
Objective: Description of knowledge on prevention of surgical site infections (SSIs) among medical staff in Son Tay general hospital, 2021 and some related factors.Method: A cross-sectional study was conducted on 151 medical staff.Results: The rate of medical staff with fully knowledge of SSI prevention is 36.42%, in which the rate of doctors is 38.3% and of nurses is 35.58%. Age group ≥30 (OR=2.82; 95%CI: 1.12 – 7.13);Department of Surgery (OR=13.61; 95%CI: 5.14 – 35.98); working year ≥10 (OR=2.54; 95%CI: 1.26 – 5.11) and number of patients cared for/day
Keywords: Knowledge; surgical site infection; medical staff, hospital-acquired infection.